1986
DOI: 10.1520/jfs12284j
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Sharp Force Fatalities—A Comprehensive Forensic Medical Study

Abstract: A ten-year series of 142 homicidal fatalities caused by sharp force injury was studied with the aim to systematize information inherent in the characteristics of the victim and the pattern of injuries. The population of victims consisted of 112 males (79%) and 30 females (21%); among perpetrators, 125 (88%) were males. Among victims as well as among perpetrators, persons of non-Swedish origin were overrepresented in relation to their share of the nonselected population. In 82 cases (58%), one or two wounds had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
57
3
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 3 publications
12
57
3
2
Order By: Relevance
“…Successful analysis and interpretation can provide important contextual information regarding the instant of trauma, such as the position of the victim in relation to the attacker, the handedness of the attacker, whether the wound was caused by suicide or homicide etc. [for example 2,4,5,6,7]. Furthermore, the motion of the sharp object can be ascertained depending on whether a cut (the incision is wider than it is deep) or stab (the incision is deeper than it is wide) mark is left [see 8 for trauma definitions].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful analysis and interpretation can provide important contextual information regarding the instant of trauma, such as the position of the victim in relation to the attacker, the handedness of the attacker, whether the wound was caused by suicide or homicide etc. [for example 2,4,5,6,7]. Furthermore, the motion of the sharp object can be ascertained depending on whether a cut (the incision is wider than it is deep) or stab (the incision is deeper than it is wide) mark is left [see 8 for trauma definitions].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has focussed on interpreting sharp-force trauma from bone in order to make statements about the context of death in both forensic and archaeological contexts. Such work includes the definition of kerf dimensions and properties [9,10], the differentiation of cutmark origin [9,10,11,12,13,14], the impact of other taphonomic processes on cutmark preservation [15,16], patterns of butchery and dismemberment [10,17,18,19] and describing the details of the trauma incident itself [1,2,4,5,6,7,20,21]. Although research has demonstrated that it is possible to distinguish the class of sharp object used from the mark left behind, it is difficult to be any more precise than that.…”
Section: Introductionmentioning
confidence: 99%
“…However, tool marks identification on bone is under researched with the majority of sharp blade trauma focused on knife [1][2][3][4] and saw tool marks [5][6]. The four studies on Samurai sword trauma derived from archaeological specimens [7][8][9][10] and only one study from a forensic context [11].…”
Section: Discussionmentioning
confidence: 99%
“…The blade holder design allows for easy interchange of blades for testing. The knives most commonly used in stabbing incidents are those household knives which are most readily available [13]. Three knives commonly available in the household have been tested; a cook's knife, a carving knife and a utility knife (shown in Fig.…”
Section: Methodsmentioning
confidence: 99%